TAG Plume: Revisiting the Hydrothermal Neodymium Contribution to Seawater - Stichel, Torben; Pahnke, Katharina; Duggan, Brian; Goldstein, Steven L.; Hartman, Alison E.; Paffrath, Ronja; Scher, Howie D. (Frontiers in Marine Science, 2018)
We present results on the distribution of εNd and [Nd] from the TAG hydrothermal vent field and adjacent locations collected during the GEOTRACES GA03 cruise in October 2011. Our results show that Nd isotopes directly below and above the plume do not significantly deviate from average NADW (εNd = −12.3 ± 0.2). Within the plume, however, isotope values are shifted slightly toward more radiogenic values up to εNd = −11.4. Interestingly at the same time a significant decrease in [Nd] along with rare earth element (REE) fractionation is observed, indicating enhanced scavenging within the plume despite the change in Nd isotopes. Elemental concentrations of Nd are reduced by 19.6–18.5 pmol/kg, coinciding with the maximum increase of mantle derived helium (xs3He) from 0.203 to 0.675 fmol/kg, resulting in an average 1.8 pmol/kg decrease in [Nd] relative to an expected linear increase with depth. The inventory loss of Nd within the plume sums up to 614 nmoles/m2, or 6%, if a continuous increase of [Nd] with depth is assumed. Compared to BATS and the western adjacent station USGT11-14, the local inventory loss is even higher at 10%. The tight relationship of xs3He increase and [Nd] decrease allows us to estimate scavenging rates at TAG suggesting 40 mol/year are removed within the TAG plume. A global estimate using power output along ocean ridges yields an annual Nd removal of 3.44 × 106 mol/year, which is about 71% of riverine and dust flux combined or 6–8% of the estimated global flux of Nd into the ocean. The change in Nd isotopic composition of up to 0.7 more radiogenic εNd values suggests an exchange process between hydrothermally derived particles and seawater in which during the removal process an estimated 1.1 mol/year of hydrothermal Nd is contributed to the seawater at the TAG site. This estimate is only 0.1% of the global Nd signal added to the ocean by boundary exchange processes at ocean margins, limiting the ability of changing the Nd isotopic composition on a global scale in contrast to the more significant estimated sink of elemental Nd in hydrothermal plumes from this study.